Optimization of the processing mode of machine tools by using the criterion of minimum cost - A. M., Ahmed Alwaise; Usubamatov, Ryspek, Prof. Dr.; Zuraidah, Mohd Zain, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.